13‐4: Progress of Highly Efficient Blue TADF Emitter Materials Towards Mass Production. Issue 1 (30th May 2018) - Baumann, Thomas; Budzinsky, Matthias
Abstract : OLED panel makers are anxiously waiting for a highly efficient blue emitter for a significant improvement of their panels. In this paper, we present the best high‐efficiency blue OLED to our knowledge with an EQE of 14% and a lifetime LT97 at 700 nits of 10 hours.